STRESS AND ITS IMPACT ON INDIVIDUAL BEHAVIOR - Ulviyya Guliyeva (Modern Scientific Technology, 2025)
Stress, as an integral part of human life, has a profound impact on the psychological, physiological and behavioral levels of an individual. At the psychological level, stress causes behavioral changes such as emotional tension, anxiety, depression, aggression and social isolation. Cognitive functions, attention, memory and decision-making ability weaken under stress. At the physiological level, stress increases the secretion of hormones (adrenaline, cortisol), affects the cardiovascular and immune systems, and can disrupt digestion and sleep processes. The impact of stress on individual behavior is multifaceted: changes in social relationships, risky decision-making, the emergence of maladaptive habits and a decrease in the quality of daily life are observed. However, mild stress (eustress) increases individual motivation and performance. Stress management is important for maintaining the psychological and physiological health of an individual. Effective intervention strategies include cognitive-behavioral therapy, meditation, physical activity, social support, time management and adaptive behavioral mechanisms. These strategies help to normalize individual behavior and improve the quality of life by minimizing the negative effects of stress. As a result, stress plays an important role in shaping both individual behaviors and quality of life. Understanding and managing stress is important for both academic, professional and personal life